2022
DOI: 10.2478/helm-2022-0018
|View full text |Cite
|
Sign up to set email alerts
|

Endoparasites of wild boars (Sus scrofa) in Primorsky Krai, Russia

Abstract: Summary This study identified helminthic species among wild boars (Sus scrofa) in Primorsky Krai, Russia. In total, 66 fecal samples were taken from wild boars and examined using the floatation-sedimentation method to identify helminths eggs and protozoan cysts. Age and sex were estimated for each host animal investigated. The helminthic fauna of the wild boars examined involved six parasite genera, but 4 are helminths and 2 are protozoans: the nematodes Metastrongylus spp., Trichuris suis, Capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…The prevalence of A. suum infection in suburban wild boars (7.1%) is lower than previously noted among suburban wild boars in Belgrade (9.37%) [29]. A. suum has been found in wild boar in Poland [30], Spain [31], Brazil [24], Russia [18], and Finland [32]. Also, our data indicate that, while A. suum was not present in lighter animals, i.e., under 40 kg, it was found in 21.1% of individuals in the 40-70 kg range.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The prevalence of A. suum infection in suburban wild boars (7.1%) is lower than previously noted among suburban wild boars in Belgrade (9.37%) [29]. A. suum has been found in wild boar in Poland [30], Spain [31], Brazil [24], Russia [18], and Finland [32]. Also, our data indicate that, while A. suum was not present in lighter animals, i.e., under 40 kg, it was found in 21.1% of individuals in the 40-70 kg range.…”
Section: Discussionmentioning
confidence: 90%
“…Another study conducted in Northwestern Poland recorded an infection rate of 58.8% in forest-dwelling wild boar [15]. Other authors have also identified Eimeria protozoa in these animals, with extensities of 33.33% in Italy [16], 7.5% in Bulgaria [17], and 3% in Russia [18]. Such variation can be related to environmental factors (e.g., warmer winters).…”
Section: Discussionmentioning
confidence: 99%
“…Although the helminth parasites of domestic pigs are well documented, little information is available about the intestinal helminth infections of wild boar Sus scrofa (Linnaeus, 1758) [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%